Fiscal Rules for the Western Balkans - Kikoni, Edith; Madzarevic-Sujster, Sanja; Irwin, Tim; Jooste, Charl (World Bank, Washington, DC, 2019)
Policy toward fiscal rules is an important issue in the countries of the Western Balkans (Albania, Bosnia and Herzegovina, Kosovo, Montenegro, North Macedonia, and Serbia). According to a rough estimate, the countries with rules (all but North Macedonia) have complied with their debt and overall-deficit rules a little more than half the time. An online survey, conducted for this paper, suggests that public understanding of the rules is limited, which may reduce the political pressure for compliance. To get debt down to prudent levels, Albania and Montenegro will need a strong commitment to complying with their fiscal rules and will often have to do more than their deficit rules require. The following principles should guide future policy toward fiscal rules: more emphasis should be given to ensuring that fiscal rules are widely understood and enjoy the support of a broad range of stakeholders; policy toward the rules should be consistent with accession to the European Union, but the rules should be simpler than the European Union's and the debt limits lower; limits in rules should not be mistaken for targets; and public financial management should be improved to support the implementation of rules.